Unmasking cerebral infarction: hemianopia and heavy menstrual bleeding in a patient with adenomyosis and vascular abnormalities - Qing Wan; Chao Wang; Weiyue Zhang; Weijia Zhong; Haoran Wang; Hee King SU; Mei Hwa Joanne HNG; Fan Yang; Xiaoguang Li (International Journal of Emergency Medicine)
Abstract Background Adenomyosis, typically associated with heavy menstrual bleeding and pelvic pain, is rarely linked to neurological complications. This case presents a rare instance of ischemic stroke in a young patient with adenomyosis and vascular abnormalities, underscoring the role of anemia, hypercoagulability, and vascular factors as potential contributors to cerebral infarction. Case presentation We describe a 41-year-old female with a history of adenomyosis who presented with right-sided hemianopia and dizziness following severe menstrual bleeding. Imaging revealed multiple acute cerebral infarctions and diffuse narrowing of the left internal carotid artery, suggesting an underlying vascular pathology. Thrombelastography revealed a hypercoagulable state, raising questions about the contributions of systemic and vascular factors in the context of adenomyosis. Conclusion This case highlights the need for a multidisciplinary approach in young patients with atypical risk factors. The findings underscore the importance of considering gynecological, vascular, and coagulation abnormalities in the evaluation of cerebrovascular events, offering new insights into diagnostic and therapeutic strategies.